2020
DOI: 10.1177/1078087420926648
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Trade-Offs Local Governments Make in the Pursuit of Economic Growth and Equity

Abstract: Economic development at the municipal level often necessitates that local governments make trade-offs between firm- and locality-based strategies. In recent decades, economic development researchers have described these efforts over time as exhibiting certain patterns and metaphors: as a series of waves, as embodying a type of lock-in effect, and as a policy layering process; however, the mechanisms behind these patterns remain unclear. This article draws upon 30 years of economic development policy decision m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…Smaller governments and those with less organizational capacity faced greater obstacles (Terman and Feiock 2015) and were less likely to make longer‐term commitments. This is consistent with our own research that resource capacity is a key factor in whether local governments are able to engage in equity‐oriented development (Stokan, Deslatte, and Hatch 2020). Local governments across the United States have made demonstrable strides in sustainability planning, capacity building, and performance over the last decade (Hawkins et al 2016; Swann and Deslatte 2019).…”
Section: Federal Government Fiscal Stimulus and Social Equitysupporting
confidence: 92%
See 1 more Smart Citation
“…Smaller governments and those with less organizational capacity faced greater obstacles (Terman and Feiock 2015) and were less likely to make longer‐term commitments. This is consistent with our own research that resource capacity is a key factor in whether local governments are able to engage in equity‐oriented development (Stokan, Deslatte, and Hatch 2020). Local governments across the United States have made demonstrable strides in sustainability planning, capacity building, and performance over the last decade (Hawkins et al 2016; Swann and Deslatte 2019).…”
Section: Federal Government Fiscal Stimulus and Social Equitysupporting
confidence: 92%
“…Recent research suggests there are factors that determine which trajectory governments pursue (Deslatte and Stokan 2019). Localities make trade‐offs between traditional firm‐based approaches focusing on tax abatements and TIFs and alternative approaches featuring job training assistance, community development loans, entrepreneurship and sustainability (Stokan, Deslatte, and Hatch 2020). These trade‐offs are explained by three factors: (1) local government competition for economic development, (2) organizational capacities (financial, technical, political), and (3) organizational interconnectedness—the set of actors that are present to influence policy selection (e.g., government and private sector actors).…”
Section: Local Governments Have Struggled With Equitable Development mentioning
confidence: 99%
“…Third wave strategies sought to bolster their entrepreneurial ecosystem through business incubators and specialized training. Finally, fourth wave strategies have been broadly conceived as prioritizing community development, environmental sustainability, and improving social equity ( Deslatte and Stokan 2019 ; Filion, Reese and Sands 2021 ; Osgood, Opp and DeMasters 2016 ; Stokan, Deslatte and Hatch 2021 ; Wilson and Polter 2020 ). Previous research has shown that governments use a mix of strategies ( Lowe and Feldman 2018 ), may return to prior approaches during recessions ( Warner and Zheng 2013 ; Zheng and Warner 2010 ), and that policy layering may better reflect these transitions given continued usage of earlier strategies ( Stokan, Deslatte and Hatch 2021 ).…”
Section: Local Economic Development and Covid-19mentioning
confidence: 99%
“…Indirectly, sustainable economic development can be directly carried out as a form of support for the regional economy, which continues to be pursued as a priority for national development in general, such as education, health and others. This is institutional and very beneficial for the economic growth of a region (Al-Qudah et al, 2021;Ehigiamusoe and Samsurijan, 2021;Gruzina et al, 2021;Langroodi, 2021;Pradhan et al, 2021;Pulido-Fernández and Cárdenas-García, 2021;Stokan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%